PENGARUH MEDIA PEMBELAJARAN LITERASI BERBASIS E-MODUL TERHADAP PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR (STUDI Literatur) - Indah Putria Syafa; Meliyana Putri; Nurul Zahro Eka Setiawati; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Literacy is the most important part of the learning process. This is because students who carry out literacy activities to the maximum, of course, will get more learning experience compared to other students. However, in reality, the rapid development of technology is currently the trigger for students' low interest in literacy in elementary schools. Students are more interested in using this technology as a medium of entertainment or just playing games than as a medium of literacy. This study aims to find out an explanation of the influence of E-Module-based literacy learning media on the character building of elementary school students. The method used in this research is descriptive research with a qualitative approach. The data collection technique used is literature study (literature study). Sources of data Libraries or literature in this study were taken from printed books, scientific journals, and online news articles which contain information about the issues to be discussed. The results showed that there was an influence of E-Module-based literacy learning media on the character-building of elementary school students. Keywords: : Literacy, E-Module, Character